Verification, model checking, and abstract interpretation : 18th International Conference, VMCAI 2017, Paris, France, January 15-17, 2017, Proceedings /: 18th International Conference, VMCAI 2017, Paris, France, January 15-17, 2017, Proceedings. (2017) - Unknown
No abstract available